Effects of modified fasting therapy on tongue coating and gut microbiome in overweight and obese adults: a controlled clinical trial - Zeng, Dongkai; Zhang, Tingying; Zhu, Yunling; Feng, Jiahao; Ye, Ziheng; Zhao, Jin; Huang, Peng; Zhang, Li; Liu, Taoli (Frontiers in Nutrition, 2026)
IntroductionCaloric restriction facilitates weight loss and metabolic improvement, in part by altering the gut microbiota. However, its influence via the tongue coating microbiota and gut microbiota remains largely unexplored.MethodsTo address this gap, we conducted a single-center, prospective, controlled study from 23 April to 5 July 2021, enrolling 48 participants with a body mass index (BMI) ≥ 24 kg/m2. Participants were assigned to either a 7-day modified fasting group (550 kcal/day, n = 35) or a control group (n = 13) based on their personal preference.ResultsIn the fasting group, body weight decreased by 4.0 ± 1.6 kg (p < 0.01), BMI decreased by 1.51 ± 0.58 (p < 0.01), significantly, accompanied by marked improvements in blood glucose and lipid profiles (p < 0.05). 16S rRNA sequencing of tongue coating and fecal samples revealed distinct microbial alterations between groups. In the tongue microbiota, Haemophilus was reduced, while Prevotella and Actinomyces were enriched, along with suppression of nucleotide synthesis and glycolysis pathways. In the gut microbiota, Bacteroides decreased, and Clostridia increased, with significant upregulation of gluconeogenesis and branched-chain amino acid biosynthesis pathways (p < 0.05). Notably, specific taxa such as Haemophilus and Granulicatella were positively correlated with body weight and BMI (r > 0.4, p < 0.05).DiscussionThese findings suggest that MFT improves metabolic outcomes by reshaping the taxonomic composition and possible functional capabilities of the tongue coating and gut microbiota in overweight and obese individuals. However, these findings should be interpreted in the context of the limitations of the study, including its non-randomized design and the preliminary nature of the gut microbiome analysis due to a small sample size.Clinical trial registrationhttp://www.chictr.org.cn/, identifier ChiCTR2100047532.